OPTIMALISASI KESADARAN WAJIB PAJAK DI DESA SUTAWINANGUN KECAMATAN KEDAWUNG KABUPATEN CIREBON - Dadang Suhardi; Munir Nur Komarudin; Deri Prayudi (POLITEKNIK LP3I JAKARTA, 2022)
This Community Service (PkM) aims to optimize taxpayer awareness in Sutawinangun Village, Kedawung District, Cirebon Regency. The method used is tax information and socialization introduction, as well as a participatory approach by involving the community in tax education programs. This PkM involves taxpayers consisting of traders, farmers, and informal sector workers. The results of this study show that through an effective participatory approach and tax education, taxpayer awareness can be significantly increased. This is evidenced by the increasing number of taxpayers who pay taxes regularly and the increasing revenue from taxes. Tax information and socialization introduction and a participatory approach in tax education programs are effective strategies to increase taxpayer awareness. In this PkM, several steps are taken to achieve the goal of optimizing taxpayer awareness. First, identification of problems related to low taxpayer awareness and its causes. Next, a tax education program is designed that involves the community in a participatory manner. The program includes providing information on the importance of paying taxes, how to calculate and pay taxes, as well as the benefits of taxes for village development.Keywords: Optimization, Taxpayer Awareness, Property Tax